2013
DOI: 10.1080/10498850.2013.771390
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Physical, Chemical, and Microbiological Assessment of Blue Shrimp (Litopenaeus stylirostris) Stored in Ice

Abstract: Postmortem changes in blue shrimp (Litopenaeus stylirostris) muscle were studied on the basis of biochemical, chemical, physical, and microbiological changes during an 18 day storage period at 0 • C. Adenosine 5 -triphosphate (ATP) content, breakdown products, K-value, pH, trimethylamine nitrogen (TMA-N), total volatile basic nitrogen (TVB-N), water holding capacity (WHC), color, and texture (shear force) changes were examined. Also, total mesophilic and psychrophilic bacterial counts were measured. K-value in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The pH of fish flesh has an important influence on its tendency to deteriorate because of its control on bacterial growth. [33] However, an animal's nutritional stage and high stress or exercise levels before an animal's death modify the glycogen concentration stored in muscle, consequently influencing in the post mortem pH. [34,35] In the present study, the pH for croaker fish was significantly (p < 0.05) higher (7.29) than squid and white leg shrimp fresh meat ( Table 1).…”
Section: Resultsmentioning
confidence: 47%
“…The pH of fish flesh has an important influence on its tendency to deteriorate because of its control on bacterial growth. [33] However, an animal's nutritional stage and high stress or exercise levels before an animal's death modify the glycogen concentration stored in muscle, consequently influencing in the post mortem pH. [34,35] In the present study, the pH for croaker fish was significantly (p < 0.05) higher (7.29) than squid and white leg shrimp fresh meat ( Table 1).…”
Section: Resultsmentioning
confidence: 47%
“…Four texture parameters including hardness, springiness, cohesiveness and chewiness in P‐Ds groups first rise and then drop with increase in the DH of PHSDEW, which was in accord with water retention's results (Table ). The PHSDEW‐DH3% group was higher than SC and MP groups ( P < 0.05), and numerous studies confirmed that the parameters of texture would reduce during storage (Canizales‐Rodríguez et al ., ; Zhang et al ., ). Therefore, the result indicated that the use of PHSDEW‐DH3% improved the texture of the cooked shrimp after chilling.…”
Section: Resultsmentioning
confidence: 97%
“…WHC with different storage times were shown in Table , significant decrease was observed between initial WHC or 30 days storage and the final WHC of shrimp samples ( p < .05), but there was no significantly difference of other different storage time ( p > .05). The decrease of WHC is often described as the effect on denaturation of myofibrillar protein in the muscle during cold storage (Canizales‐Rodríguez et al, ; Olsson, Ofstad, Lodemelc, & Olsen, ). In this study, the precooked treatment had changed the muscle structure of shrimps, which can cause network contraction of myofibril, myosin protein deformation and increase extracellular space (Aaslyng, Bejerholm, Ertbjerg, Bertram, & Anderson, ; Jantakoson, Kijroongrojana, & Benjakul, ), so the effect of freezing denaturation on shrimp proteins was not significant with the increasing storage time within 150 days ( p > .05).…”
Section: Resultsmentioning
confidence: 99%